A highly efficient and sensitive LC‐MS/MS method for the determination of afatinib in human plasma: application to a metabolic stability study. (24th January 2016) - Kadi, Adnan A.; Abdelhameed, Ali S.; Darwish, Hany W.; Attwa, Mohamed W.; Al‐Shakliah, Nasser S.
Abstract: Afatinib (AFT) is a new tyrosine kinase inhibitor approved for the treatment of nonsmall cell lung cancer. In the present study, a simple, specific, rapid and sensitive liquid chromatography tandem mass‐spectrometric method for the quantification of AFT in human plasma, was developed and validated. Chromatographic separation of the analytes was accomplished on a reversed‐phase Luna ® ‐PFP 100 Å column (50 × 2.0 mm; 3.0 μm) maintained at ambient temperature. Isocratic elution was carried out using acetonitrile–water (40:60, v/v) containing 10 mm ammonium formate buffer (pH 4.5) adjusted with formic acid at a flow rate of 0.4 mL min −1 . The analytes were monitored by electrospray ionization in positive ion multiple reaction monitoring mode. The method yields a linear calibration plot ( r 2 = 0.9997) from a quantification range of 0.5–500 ng mL −1 with the lower limit of quantification and lower limit of detection of 1.29 and 0.42 ng mL −1, respectively. The intra‐ and inter‐day precision and accuracy were estimated and found to be in the ranges of 1.53–4.11% for precision and −2.80–0.38% for accuracy. Finally, quantification of afatinib in a metabolic stability study in rat liver microsomes was achieved through the proposed method. Copyright © 2016 John Wiley & Sons, Ltd.